Images of the Self and the Other in the Columns by Jordi Soler in the Spanish and Mexican Press - Emmy Poppe; Dagmar Vandebosch (Contextes, 2013)
Drawing on Dominique Maingueneau’s concept of ethos and on Ruth Amossy’s theory of doxa and the function of stereotypes in the presentation of the Self, this article studies the evolution of ethos in the literary journalism of the Mexican writer Jordi Soler. It does so in two corpora of columns set in two specific temporal and geographic settings: on the one hand, Mexico in the period between 1990 and 1995, the years in which the much-debated North American Free Trade Agreement (NAFTA) between Canada, the USA and Mexico was being negotiated and implemented; and Europe in the increasingly ‘global era’ of the first decade of the 21st century, on the other hand. More particularly, it analyses the way Soler’s identity as enunciator is constructed in relation to that of a cultural ‘other’ represented by the United States, and how this relation between the Self and the US ‘other’ evolves over time, showing a strong shift with respect to the role of the image of the other in the construction of ethos. In the first corpus a collective and national ethos, based on a strict opposition between Mexican and US cultural identities, prevails over a more individual, liberal ethos which is strongly contrasted with the US image. In the more recent columns, on the contrary, the construction of both the Self and the Other is more ambivalent, dynamic and heterogeneous, an evolution due mainly to the reduction of the part national identity plays in the construction of the Self, and to the affirmation of individual over collective ethos.